Innovation on Distant Hybridization of Saline-tolerant Mud Flat Spartina and Rice Germplasm - Chen, Qikang; Chen, Bo; Lu, Huilan; Zhou, Hui; Mei, Zhiping (Asian agricultural research, 2016)
To explore saline-tolerant high yield Spartina and rice germplasm resources,innovate upon distant hybridization technology,and develop new saline-tolerant mud flat Spartina germplasm,autonomous patent for invention was used to study distant hybridization of Spartina and rice in 2005- 2016. The study adopted tidal flat planting screening,phenotypic screening,molecular marker assisted selection,to find biological evidences of new germplasm,and also applied crossbreeding,conventional breeding,and molecular breeding,to select new saline-tolerant Spartina and rice varieties. With 12 years of efforts,the team developed 1498 crossbreeding combinations and established pedigree file and seed bank,tested 307 crossbreeding materials(57 hybrid seeds showed parental genetic components of Spartina and Rice); obtained Spartina/ Rice distant hybridization and seed setting,transplanting,hybridization material economic traits,and molecular biological experimental evidences; Rice♀× Spartina ♂ hybridization success rate of 1. 04- 1. 39%; obtained authorization of patent for invention of Distant Hybridization Methods for Spartina and Rice; formulated procedures for high yield cultivation of Spartina-Rice,planted 33. 33 hm2Spartina-Rice in coastal saline and alkaline land,cultivated 10 new saline-tolerant Spartina-Rice varieties,and the rice yield up to 5. 925- 8. 28 t / hm2. Results indicate that Spartina-Rice is saline-tolerant high yield rice germplasm,developed through sexual hybridization,conventional breeding,and molecular breeding technologies,and is optimal crop for saline and alkaline land. Success of Spartina-Rice solves the problem of saline-tolerant crop badly for transformation of saline and alkaline land,the problem of feeds for herbivores,as well as problem of environmental pollution resulted from straw burning. Besides,it is of essential scientific significance for resource utilization,increase of agricultural efficiency,grain security,and farmland strategy,so it has broad application prospect.